2017
DOI: 10.1039/c7sc03777e
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic carbenes on close-packed coinage metal surfaces: bis-carbene metal adatom bonding scheme of monolayer films on Au, Ag and Cu

Abstract: N-Heterocyclic carbenes wet the solid surfaces of group 11 metals with energetically favourable electron donating biscarbene metal complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
144
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(161 citation statements)
references
References 75 publications
15
144
0
2
Order By: Relevance
“…The high affinity of NHCs towards metal, metal‐oxide and semimetal surfaces along with their wide chemical tunability have made NHCs an attractive alternative to thiols for generation of SAMs. It has been widely demonstrated that the anchoring geometry of NHCs on surfaces is directed by the steric properties of their substituents (Scheme , top panel) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high affinity of NHCs towards metal, metal‐oxide and semimetal surfaces along with their wide chemical tunability have made NHCs an attractive alternative to thiols for generation of SAMs. It has been widely demonstrated that the anchoring geometry of NHCs on surfaces is directed by the steric properties of their substituents (Scheme , top panel) …”
Section: Introductionmentioning
confidence: 99%
“…NHCs with small side groups, such as methyl (marked by yellow disks in Scheme ), which do not lead to strong lateral interactions, form planar bis‐carbene metal complexes on metal surfaces . NHCs with larger dimethyl substituents formed films with mixtures of flat and upright orientations, whereas surface‐anchored NHCs with larger diisopropyl and diisopropylphenyl groups (marked by blue spheres in Scheme ) were detected only in an upright position .…”
Section: Introductionmentioning
confidence: 99%
“… 32 35 The structure and stability of surface anchored NHCs were studied by several surface-sensitive techniques. 36 38 However, in depth analysis of the chemical and structural properties of chemically-active NHCs, which were recently utilized as indicators for surface induced reactivity, 23 , 25 remains rare.…”
Section: Introductionmentioning
confidence: 99%
“…-Heterocyclic carbenes (NHCs) are molecular ligands characterized with strong affinity to metals 1,2 . The strong NHC-metal interaction enabled the formation of stable self-assembled monolayers (SAMs) of NHCs on metals [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] , metal-oxides 22,23 and semimetals 24 . The wide chemical-tunability of NHCs led to utilization of NHC-based SAMs as biosensors 10,25,26 , molecular probes for surface reactivity [27][28][29] , and co-catalysts 3,[30][31][32][33] .…”
mentioning
confidence: 99%